(untitled) (Jurnal Pilar Nusa Mandiri, 2020)
Every year, routinely PT. Enseval Putera Megatrading held several events which were held face-to-face and online and involved many parties, from the employees’ board of directors and external parties as sources. The events held include: National Work Meeting (RAKERNAS), Mid Year Work Meeting, Product Launching, EMDP Graduation, Enseval Anniversary, Innovation Forum, and others. There are at least 3 stages that the Event Owner must go through in organizing and achieving the goals of an event, pre-event starting from the formation of the committee to determining the concept of the event that will take place, running events starting from registering participants who are present in the event to maintaining the event’s run down, post events ranging from gathering feedback on events to publishing materials. An event management system is absolutely necessary to support the success of the event. Valent, which is a React Native based mobile application, is the right step to answer this need. React native is an application that is used using the JavaScript programming language to create applications in developing applications on smartphones based on Android and iOS. (Zammetti, 2018) This allows Valent to run on 2 OSes at once (Android & IOS) so that all event participants can enjoy the benefits of the Valent application directly from their respective smartphones.